Spinal Manipulative Therapy Alters Brain Activity in Patients With Chronic Low Back Pain: A Longitudinal Brain fMRI Study - Tan, Wenli; Wang, Wei; Yang, Yuchan; Chen, Yilei; Kang, Yingjie; Huang, Yanwen; Gong, Zhigang; Zhan, Songhua; Ke, Zeng; Wang, Jianwei; Yuan, Weian; Huang, Weiyuan; et al. (Frontiers in Integrative Neuroscience, 2020)
Background: Spinal manipulative therapy (SMT) helps to reduce pain of patients with chronic low back pain (cLBP). However, the underlying mechanism of SMT for pain relief and brain response to pain treatment remains unclear. We utilized brain functional magnetic resonance imaging (fMRI) to assess the effect of spinal manipulative therapy (SMT) on patients with chronic low back pain (cLBP) in response to real-time mechanical stimulus. Methods: Patients with cLBP (group1, 14 participants) and age-matched healthy participants (group2, 20 participants) were prospectively enrolled. FMRI was performed for group1 at three time-points: before SMT (TP1), after the first session of SMT (TP2) and after the sixth session of SMT (TP3). During the fMRI scanning, a real-time focal mechanical stimulus was applied to the low back area. Similar to those in Group1, the participants in Group2 underwent fMRI once under real-time focal mechanical stimulus, but received no SMT. Clinical questionnaires for pain and quality of life were obtained from participants in group1. Results: Before SMT at TP1, there was no significant difference in brain activity between group1 and group2. After the first session of SMT at TP2, there was significantly greater brain activity in group1 in the right parahippocampal gyrus, right dorsolateral prefrontal cortex and left precuneus than in group2 (P<0.05). After the sixth session of SMT at TP3, there was significantly greater brain activity in the posterior cingulate gyrus and right inferior frontal gyrus in group 1 than in group 2 (P<0.05). Group1 showed significantly decreased pain scores after SMT (P<0.001). Conclusion: SMT altered brain activity in part of the default mode network in patients with cLBP. Our study suggests that the default mode network might be the neural correlate of chronic low back pain.